Application of femtosecond laser microsurgery in assisted reproductive technologies for preimplantation embryo tagging - Ilina, Inna V. (Biomed Opt Express, 2019)
Femtosecond laser pulses were applied for precise alphanumeric code engraving on the zona pellucida (ZP) of mouse zygotes for individual embryo marking and their identification. The optimal range of laser pulse energies required for safe ZP microsurgery has been determined. ZP was marked with codes in three different planes to simplify the process of embryo identification. No decrease in developmental rates and no morphological changes of embryos post laser-assisted engraving have been observed. ZP thickness of embryos post laser-assisted code engraving has been shown to differ significantly from that of control group embryos at the hatching stage. Due to moderate ZP thinning as compared to its initial width at 0.5 dpc (days post coitum), readability of the code degrades slightly and it still remains recognizable even at hatching stage. Our results demonstrate that application of femtosecond laser radiation could be an effective approach for noninvasive direct embryo tagging, enabling embryo identification for the whole period of preimplantation development.